Penanganan Bahan (Material Handling) Terhadap Pembuatan Part Bracket Roof Rail A Dengan Menggunakan Metode General Analysis di PT Ichii Industries Indonesia - Raynanda Abdillah; Rizki Achmad Darajatun (Peneliti.net, 2022)
PT. Ichii Industries Indonesia is a company engaged in the field of Manufacturing that produces car spare parts. PT. Ichii Industries Indonesia is related to the production process where the company's goal is to carry out the production process, PT. Ichii Industries Indonesia makes a good and correct production process in order to create quality products that can continue to be marketed and produced sustainably or do not stop production. Therefore it is necessary to know about the process of making good parts in accordance with work instructions or company SOPs. This study aims to determine the amount of Material handling costs in the production process of Bracket Roff Rail A parts. The method used in this study is General Analysis, General Analysis is a logical approach that facilitates the author in analyzing and finding the best solution for Material handling problems with steps precise and careful and detailed procedures. Based on research using the General Analysis procedure method that has been carried out, it can be concluded that the Material handling cost is Rp. 88,095.99-/ meter. These costs are influenced by the use of semi-automatic machines and the use of gravity.